Using the cytogenetic dosimetry for the control of potential over exposure of contractors enterprises staff of SSE ChNPP - L. K. Bezdrobna; L. V. Tarasenko; T. V. Tsyganok; T. V. Melnyk; V. A. Kurochkina; V. O. Sushko; S. Yu. Nechayv; L. I. Shvayko; О. О. Kolosynska (Ядерна фізика та енергетика)
Cytogenetic examination of two groups of contractors staff of SSE ChNPP who performed the work on the preparation of pits for the construction of the new confinement (22 workers), and the dismantling of the “Ukryttya” ventilation pipe (12 workers) was provided. There were revealed three individuals, who had individual frequency of specific markers of radiation (dysenteric chromosomes with accompanying fragments) significantly exceeding the mean population levels and the average rate in the comparison groups of persons who had not occupational contacts with radiation factor. It indicated the probability of their additional background radiation while performing the work in the ChNPP zone. Calculated by dysenteric chromosomes frequency indicative “biological” doses of their irradiation show more significant impact of the radiation factor than that resulted from the data of physical dosimetry.